A Clinical Case Report on Managing Rasmussen’s Encephalitis in a 5-Year-Old: Use of Methylprednisolone and Antiepileptic Drugs - Nandagopal, Nandhani; Arul, Lakshmi Priya; Subramanian, Shyam Sundar (Indian Journal of Pharmacy Practice)
The article aims to describe a rare case of pediatric Rasmussen’s encephalitis, a condition characterized by chronic and progressive inflammation affecting one hemisphere of the brain. This inflammation is believed to be triggered by an immune response directed against viruses or other foreign antigens. Rasmussen’s encephalitis typically manifests with unilateral hemispheric atrophy, leading to neurological deficits and cognitive impairments over time. A 5-year-old patient presented with recurrent seizures characterized by right upper limb jerks and transient loss of consciousness. Diagnostic tests indicated Rasmussen’s encephalitis affecting the left hemisphere of his brain. Treatment commenced promptly with intravenous medications to control seizures and manage symptoms, including addressing a vitamin D deficiency. The patient responded positively to treatment, showing stabilization, and was discharged with a comprehensive management plan for ongoing care and vigilance to optimize long-term outcomes in his condition. This study aims to offer insights for future research aimed at improving survival rates and quality of life for individuals affected by this rare condition.
Keywords: Rasmussen’s encephalitis; Rare disease; Pediatric; Vitamin D deficiency; Seizures; Neurology